Habitat preferences of the grasshopper Psophus stridulus, a charismatic species of submontane pastures. Issue 4 (22nd March 2017) - Rada, Stanislav; Spitzer, Lukáš; Šipoš, Jan; Kuras, Tomáš
Abstract: Semi‐natural habitats in Europe host a substantial proportion of biodiversity, but they experience biodiversity loss due to ongoing agricultural changes. We regard the Rattle grasshopper ( Psophus stridulus ) as a charismatic species of species‐rich submontane xerothermic grasslands. To enable conservation of the species and its habitat, we studied the habitat preferences of this formerly abundant grasshopper, now threatened and declining in many European countries. In 2011, we applied capture‐mark‐recapture method to sample adults at four localities (Czech Republic), each divided into two subplots with different management and character of vegetation. In 2012, we carried out a more extensive study on habitat preferences, evaluating 179 grassland patches (24% of them occupied by P. stridulus ). For each site, we recorded vegetation characteristics (sward height and density, cover of vegetation components, percentage of bare ground), slope, inclination and agricultural management. We used multistate models in MARK software to analyse survival and movement probabilities between different subplots. Data from the 2012 large‐scale study were analysed by fitting several regression models. The results show that the species preferred south‐facing slopes with sparse, short vegetation and with patches of bare ground. Sward density was the most important predictor of species presence. For species conservation, we recommend controlling succession on the localities by regular management (grazing or cautious mowing) to maintain optimal habitat with sparse sward. We promote P. stridulus as a flagship and umbrella species of species‐rich submontane xerothermic pastures.